CRISPR‐Cas system manipulating nanoparticles signal transduction for cancer diagnosis. (5th October 2022) - Guo, Yuqian; Guo, Liang; Su, Yu; Xiong, Yonghua
Abstract: Early diagnosis of cancer is important to improve the survival rate and relieve patient pain. Sensitive detection of cancer related biomarkers in body fluids is a critical approach for the early diagnosis of cancer. The clustered regularly interspaced short palindromic repeat‐associated protein (CRISPR‐Cas) system has emerged as a molecular manipulation technology because of its simple detection procedure, high base resolution, and isothermal signal amplification. Recently, various nanomaterials with unique optical and electrical characteristics have been introduced as the novel signal transducers to enhance the detection performance of CRISPR‐Cas‐based nanosensors. This review summarizes the working mechanisms of the CRISPR‐Cas system for biosensing. It also enumerates the strategies of CRISPR‐manipulated nanosensors based on various signal models for cancer diagnosis, including colorimetric, fluorescence, electrochemical, electrochemiluminescence, pressure, and other signals. Finally, the prospects and challenges of CRISPR‐Cas‐based nanosensors for cancer diagnostic are also discussed. This article is categorized under: Diagnostic Tools > Biosensing Abstract : Table of Connects